O atendimento psicoterápico on-line: um olhar do psicólogo para o fenômeno - Rocha, Sabrina Andrade (2024)
In Brazil, the Conselho Federal de Psicologia (CFP) has issued Resolutions since the 2000s, such as Resolution numbers 12/2005, 11/2012, and 11/2018, concerning psychological services provided through Information and Communication Technology (ICT). In 2020, psychology was notably impacted by the shift to online psychological services due to the public health crisis triggered by COVID-19, which led to the suspension of in-person activities in non-essential services. Consequently, clinical psychology services migrated to online platforms. The CFP approved Resolution number 04/2020, further expanding remotely offered services. Recognizing this scenario and understanding that online psychotherapy is a new and rapidly spreading phenomenon that requires further investigation, the general objective of this research was to explore the perspectives of psychologists regarding individual online psychological care, using the guiding question: "Tell me what online psychotherapeutic care is like for you." This study is qualitative research employing the phenomenological method as a guiding approach in the interviews. Ten interviews were conducted with psychologists who provide online services. The analysis and interpretation of the data gathered from these interviews followed the methodology proposed by Critelli in *Analítica do Sentido*. The participants were psychologists with at least five years of professional experience, who are actively providing online psychological care and are registered in an online care program. The interviews revealed five main categories: (1) therapeutic bond, (2) resources and tools, (3) challenges and limitations, (4) setting, and (5) new perspectives. The results regarding the therapeutic bond in online psychotherapeutic care showed a positive perception among the participating psychologists, with many emphasizing a strong sense of connection even in the virtual environment. The discussion on resources and tools highlighted adaptive strategies used to support patients during online sessions. The setting category focused on the environment and context of online service provision, noting challenges such as privacy concerns, family interferences, and confidentiality issues. The difficulties and limitations related to online care explored barriers in non-verbal communication and concerns about the safety of both patients and professionals. Finally, new perspectives emerging from online psychotherapy were discussed, including the acceptance and benefits of this modality, the potential to increase access to care in various locations, and the development of new tools to support individuals in distress.